Evolutionary multi-agent systems : from inspirations to applications - Byrski, Aleksander; Kisiel-Dorohinicki, Marek (Springer, 2017)
This book addresses agent-based computing, concentrating in particular on evolutionary multi-agent systems (EMAS), which have been developed since 1996 at the AGH University of Science and Technology in Cracow, Poland. It provides the relevant background information on and a detailed description of this computing paradigm, along with key experimental results. Readers will benefit from the insightful discussion, which primarily concerns the efficient implementation of computing frameworks for developing EMAS and similar computing systems, as well as a detailed formal model. Theoretical deliberations demonstrating that computing with EMAS always helps to find the optimal solution are also included, rounding out the coverage.
Keywords: Multiagent systems.; Engineering.; Algorithms.; Artificial intelligence.; Computational intelligence.; elektronické knihy; electronic books